2003
DOI: 10.1191/0960327103ht358oa
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of DLa-lipoic acid against adriamycin-induced cardiac lipid peroxidation

Abstract: The cytoprotective activity of a-lipoic acid against free radical toxicity manifested during adriamycin (ADR)induced cardiotoxicity has been investigated. ADR is a potent antitumour drug known to cause severe cardiotoxicity. Although ADR generates free radicals, the role of these radicals in the development of cardiac toxicity is still not well understood. In the present study, we evaluated the influence of chronic ADR treatment on the cellular defence mechanism against free radicals and the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…The cytoprotective effects of antioxidants against DOX is usually associated with the inhibition of lipid peroxidation, regardless of the type and structure of antioxidant. 16,[42][43][44][45] Although the active antioxidants in PU extract have not been identified, its suppression of lipid peroxide formation warrants further investigation.…”
Section: )mentioning
confidence: 99%
“…The cytoprotective effects of antioxidants against DOX is usually associated with the inhibition of lipid peroxidation, regardless of the type and structure of antioxidant. 16,[42][43][44][45] Although the active antioxidants in PU extract have not been identified, its suppression of lipid peroxide formation warrants further investigation.…”
Section: )mentioning
confidence: 99%
“…α-LA has been shown by many studies, both in vivo and in vitro, to decrease lipid peroxidation levels. Reduced lipid peroxidation following α-LA administration has been observed to be associated with a protective effect against adriamycin-induced nephrotoxicity and cardiotoxicity in rats (34,35). Additional studies have found that α-LA treatment results in a decreased MDA level in the plasma (36), liver, kidney (17) and different regions of the brain (37).…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have investigated the effects of α-LA on antioxidant enzymes (35,36). Maritim et al (38) reported that α-LA administration reduced oxidative stress and altered SOD, CAT, and GSH-Px enzymatic activity levels in the liver, kidney, and heart in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, in a study carried out with the rat sepsis model, lipoic acid was shown to be able to prevent neutrophil accumulation through reducing the oxidative stress, after which lipid peroxidation increased as a result of oxidative stress, and that lipoic acid reduced the lipid peroxidation in the lungs (29). In three different studies carried out parallely, lipoic acid was reported to significantly reduce the increased lipid peroxidation (30)(31)(32). In another study, the cerebral free radical amount and the effects of reperfusion were shown to decrease through lipoic acid administration to the animals which had been exposed to ischemic reperfusion induced through cerabral artery clamping (21).…”
Section: Discussionmentioning
confidence: 99%